Letter from J. Wellen of Crest Haven Memorial Park, to Max Bredig - Wellen, J. (1944)
Letter from J. Wellen of Crest Haven Memorial Park, to Max Albert Bredig (1902-1977).
Keywords: Bredig, Georg, 1868-1944; Bredig, Max Albert, 1902-1977; Cemeteries